Study of Corn Silage Storage Management to Support Ruminant Livestock Nutrition - Hajar Hajar; La Panga (Fakultas Teknologi Pertanian Unsultra, 2025)
Ruminant livestock productivity in Indonesia remains low, largely due to the lack of a consistently available supply of highly nutritious feed. Utilizing agricultural waste, such as corn, as a base material for silage is a potential solution to address feed constraints. Corn-based silage can provide consistent feed throughout the year and boasts a relatively high nutritional content. However, the main challenges with its use are long-term storage and stability against air exposure, which are crucial for feed quality and safety. Several studies have shown that extending storage time can improve digestibility, but can also increase the likelihood of silage quality degradation if storage methods are not optimal. Issues such as reduced nutritional value, the emergence of harmful microorganisms, and the risk of mycotoxin contamination are key concerns that must be addressed. Therefore, the objective of this study is to examine how storage time affects the nutritional quality of corn silage and to analyze the effectiveness of different storage methods in maintaining aerobic stability and preventing spoilage, particularly under complex tropical climate conditions. Corn silage quality is influenced by storage methods, fermentation time, and environmental temperature and humidity. Anaerobic storage using silos or airtight plastic with high compaction effectively maintains a low pH and prevents contamination. Optimal fermentation takes 60–90 days, while longer storage can degrade quality. Corn's high carbohydrate content supports good fermentation, making it a superior feed source during the dry season.